Cascadas conservadoras aplicadas a la predicción de tráfico multifractal - Contreras Ávila, Lidia Soraya; Ospina García, Gabriel Armando; Alzate Monroy, Marco Aurelio (Ingeniería, 2005)
In this paper we propose a novel traffic prediction method, based on the statistical analysis of the coefficients of a multifractal wavelet model. The predictor is computationally efficient because it is based on a simple equation on the coefficients of the wavelet transform. It is also highly accurate because it takes into account several higher order statistics over a wide range of time scales. We verify these characteristics using the predictor over several real traffic traces.